2021
DOI: 10.1080/14778238.2021.1919573
|View full text |Cite|
|
Sign up to set email alerts
|

Configuring foreign market knowledge and opportunity recognition capabilities to predict the performance of export-manufacturing firms

Abstract: Export-manufacturing firms survive and ultimately succeed when they can accumulate, harvest,and utilise foreign knowledge to better marshal the capabilities to recognise opportunities. Prior studies are replete with a single solution by combining foreign market knowledge (FMK) and firm performance. A shift from contingent theory to the configurational approach suggests that there are multiple solutions available to achieve intended outcomes. Based on the equifinality assumption, we configure FMK in conjunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…In this context, Torres (2011) andNavarro-García et al (2016) have suggested that export firms need to develop foreign market intelligence capabilities before launching a new market/ country with a new product that can help the firm adapt to new markets/country's culture, competition and consumers' taste and preferences. Mostafiz et al (2022) have found that foreign market knowledge (FMK) and opportunity recognition capabilities positively impact the performance of Bangladesh's export manufacturing firms. Moreover, Kohli and Jaworski (1990) advocated developing market intelligence capability, which mitigates the foreign market uncertainties and favours enhanced firm performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Torres (2011) andNavarro-García et al (2016) have suggested that export firms need to develop foreign market intelligence capabilities before launching a new market/ country with a new product that can help the firm adapt to new markets/country's culture, competition and consumers' taste and preferences. Mostafiz et al (2022) have found that foreign market knowledge (FMK) and opportunity recognition capabilities positively impact the performance of Bangladesh's export manufacturing firms. Moreover, Kohli and Jaworski (1990) advocated developing market intelligence capability, which mitigates the foreign market uncertainties and favours enhanced firm performance.…”
Section: Discussionmentioning
confidence: 99%
“…Mostafiz et al. (2022a, b) and Yin et al. (2020) halt this general trend and emphasise why context matters in the EO rent-yielding process.…”
Section: Contributions Implications and Conclusionmentioning
confidence: 99%
“…The insights into the complex native and immigrant entrepreneurship setting in an emerging economy context are more actionable than if one analytical technique was used. The original survey data or calibrated score from fsQCA can be used to perform NCA (Mostafiz et al, 2021b). However, the authors used the fsQCAcalibrated scores to perform an NCA to maintain consistency.…”
Section: Eo and Km Processesmentioning
confidence: 99%
“…Learning helps to develop dynamic capabilities which enable the configuration and reconfiguration of operational resources and routines. The competitive advantage comes from a new configuration of resources and operational routines (Mostafiz et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%